A model for the training effects in swimming demonstrates a strong relationship between parasympathetic activity, performance and index of fatigue - Chalencon, S.; Busso, T.; Lacour, J.-R.; Garet, M.; Pichot, V.; Connes, P.; Gabel, C. P.; Roche, F.; Barthélémy, J. C. (PLOS ONE, 2012)
Competitive swimming as a physical activity results in changes to the activity level of the autonomic nervous system (ANS). However, the precise relationship between ANS activity, fatigue and sports performance remains contentious. To address this problem and build a model to support a consistent relationship, data were gathered from national and regional swimmers during two 30 consecutive-week training periods. Nocturnal ANS activity was measured weekly and quantified through wavelet transform analysis of the recorded heart rate variability. Performance was then measured through a subsequent morning 400 meters freestyle time-trial. A model was proposed where indices of fatigue were computed using Banister`s two antagonistic component model of fatigue and adaptation applied to both the ANS activity and the performance. This demonstrated that a logarithmic relationship existed between performance and ANS activity for each subject. There was a high degree of model fit between the measured and calculated performance (R2 = 0.8460.14,p,0.01) and the measured and calculated High Frequency (HF) power of the ANS activity (R2 = 0.7960.07, p,0.01). During the taper periods, improvements in measured performance and measured HF were strongly related. In the model, variations in performance were related to significant reductions in the level of `Negative Influences` rather than increases in `Positive Influences`. Furthermore, the delay needed to return to the initial performance level was highly correlated to the delay required to return to the initial HF power level (p,0.01). The delay required to reach peak performance was highly correlated to the delay required to reach the maximal level of HF power (p = 0.02). Building the ANS/performance identity of a subject, including the time to peak HF, may help predict the maximal performance that could be obtained at a given time.